(untitled) (Research, Society and Development, 2021)
Vertical silos are structures used by industries, the agricultural and mineral sectors to store and conserve bulk, granular or powdery solid products. However, silos are structures that can present a large number of structural and flow failures, especially due to the diversity of variables that affect structural behavior and the absence of specific national norms for calculating actions in silos. In the search for new alternatives that favor production and reduce costs without affecting the quality of the final product, the use of inserts stands out for reducing problems such as uneven discharge, segregation, partial or total obstructions in the flow, thus reducing possible productive losses to industry and problems with the physical integrity of the silo. However, the simple adoption of inserts in vertical silos without prior knowledge of some characteristics such as the most appropriate shape and dimensions for each situation may not achieve the desired result besides the fact that it generates problems in the flow of products. In view of this insecurity, the present review aimed to approach the flow behavior of stored products and the pressures that occur with the presence of insertions inside the structure, presenting results of the use of these devices in vertical silos, enabling the elaboration of safe, robust and reliable designs.